INFOGRAFIS DIGITAL WISATA BUKITTINGGI - HANIF ALHADI, Dr. Budiwirman, M.Pd., Hendra Ariwan, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
A lot of tourists visiting the city of Bukittinggi but still confused about any tourist attraction and how to locate the tourist attractions that exist in the city of Bukittinggi so that not all tours are visited by tourists, tourists still rely on asking in finding tourist locations so sacrificing a lot of time and energy.The purpose of digital infographic design is to make infographics about tourist attractions and tourist locations that are easily accessible and easy to understand, making it easier for people to know information about tourist attractions in the city of Bukittinggi, tourist locations, and introducing tourist attractions that are rarely visited by tourists.The method used in designing this infographic is a qualitative method. Qualitative research is research that is used to investigate, find, describe, and explain the quality or features of social influences that cannot be explained, measured or described.This infographic is made with the main media is an android application that is fast and easily accessible via a smartphone and made print features in the form of posters and brochures and other supporting media such as stickers, t-shirts, and totebag.Keywords: Digital Infographics, Bukittinggi Tourism